The intellectual structure of civic and Pancasila education research: trends, themes, and collaboration patterns in character education studies - Istirokhah Istirokhah; Zulkipli Lessy; Muhsin Kalida (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
This study examines the development of citizenship education, Pancasila education, and character formation through a Systematic Literature Review using PRISMA 2020 guidelines. From an initial pool of 394 articles, 15 studies published between 2015–2024 met all inclusion criteria and were analyzed through bibliometric mapping and thematic synthesis. The findings show that research collaboration in this field is still dominated by national networks, although international partnerships have increased in recent years. Research trends indicate a shift from conventional moral instruction toward digital citizenship, global value integration, and character empowerment aligned with contemporary societal demands. Thematic analysis reveals dominant focuses on digital ethics, civic identity, learning innovation, cultural negotiation, and the strengthening of reflective and participatory competencies. Overall, this review highlights that citizenship and Pancasila education have transformed into interdisciplinary spaces that support moral development, social responsibility, and adaptive civic skills. The study also identifies conceptual and methodological gaps, offering recommendations for advancing research and enriching educational practice.